2014
DOI: 10.1161/hypertensionaha.113.01251
|View full text |Cite
|
Sign up to set email alerts
|

Aldosterone and Blood Pressure Regulation

Abstract: T he purpose of this brief review is to highlight 3 recent conceptual advances in the ongoing exploration of the biology of aldosterone and how disorders of aldosterone metabolism and action lead to hypertension. Notably, important contributions to the advancement of our understanding in all 3 areas were published within the pages of Hypertension.For >60 years, the link between aldosterone and hypertension has remained a key focus of research. The focus on this hormone and how it regulates blood pressure (BP) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…Sympathoexcitation is closely associated with the development and progression of cardiovascular diseases [ 30 ]. High level of oxidative stress in the RVLM which is resulting from abnormalities of renin angiotensin system and proinflammatory cytokines is responsible for increased sympathetic outflow [ 33 , 34 ]. In this work, β -estradiol (water soluble) was used for estrogen replacement.…”
Section: Discussionmentioning
confidence: 99%
“…Sympathoexcitation is closely associated with the development and progression of cardiovascular diseases [ 30 ]. High level of oxidative stress in the RVLM which is resulting from abnormalities of renin angiotensin system and proinflammatory cytokines is responsible for increased sympathetic outflow [ 33 , 34 ]. In this work, β -estradiol (water soluble) was used for estrogen replacement.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, MR in the central nervous system controls salt appetite and neurohumoral activity and can thus regulate blood pressure at baseline and during disease. 39,40 Finally, aldosterone exerts part of its effects on the vasculature rapidly via the G protein-coupled estrogen receptor independently of the MR. 41,42 However, there are contradictory findings with respect to G protein-coupled estrogen receptor activation mediating vasoconstriction 43 or vasodilatation 44 and its role in aldosterone-induced hypertension needs to be defined.…”
Section: Blood Pressure Regulationmentioning
confidence: 99%
“…It has been confirmed both in vitro and in vivo that GPER is widely expressed in the cardiovascular system and is associated with estrogen specificity. It was also found that selective activated GPER can expand blood vessels, lower blood pressure, and inhibit vascular smooth muscle cell differentiation, making GPER an indispensable material for maintaining normal blood pressure [ 6 , 7 ]. However, these results are inconsistent with those from clinical studies.…”
Section: Introductionmentioning
confidence: 99%